HIV-1, methamphetamine and astrocytes at neuroinflammatory Crossroads - Borgmann, Kathleen; Ghorpade, Anuja (Frontiers in Microbiology, 2015)
As a popular psychostimulant, methamphetamine (METH) use leads to long-lasting, strong euphoric effects. While METH abuse is common in the general population, between 10-15% of human immunodeficiency virus-1 (HIV-1) patients report having abused METH. METH exacerbates the severity and onset of HIV-1-associated neurocognitive disorders (HAND) through direct and indirect mechanisms. Repetitive METH use decreases adherence to antiretroviral drug regimens, increasing the likelihood of HIV-1 disease progression towards AIDS. METH exposure also directly affects both innate and adaptive immunity, altering lymphocyte number and activity, cytokine signaling, phagocytic function, and CNS infiltration through the blood brain barrier. Further, METH triggers the neuronal dopamine reward pathway and leads to altered neuronal activity and direct toxicity. Concurrently, METH and HIV-1 alter the neuroimmune balance and induce neuroinflammation. Neuroinflammation modulates a wide range of brain functions including neuronal signaling and activity, glial activation, viral infection, oxidative stress and excitotoxicity. Pathologically, glial activation is a hallmark of both HIV-1 and METH-associated neuroinflammation. Significant commonality exists in the neurotoxic mechanisms for both METH and HAND; however, the pathways dysregulated in astroglia during METH exposure are less clear. Thus alterations in astrocyte intracellular signaling pathways, gene expression and function during METH and HIV-1 comorbidity, neuroinflammation and HAND are carefully reviewed. Interventions targeting astrocytes in HAND and METH are presented as potential novel therapeutic approaches.